2001
DOI: 10.1080/08098130109478014
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Research Design to Assess the Effects of Individual Music Therapy with Mentally Ill Children and Adolescents

Abstract: This paper introduces a research design to measure effects of individual music therapy with mentally ill children and adolescents on symptoms, competencies, and quality of life. In a pilot project, seven children (five boys and two girls, 4 to 11 years of age) who suffered from various mental and behavioural problems were assessed. Five children received music therapy, and two did not. The two groups were compared with regard to the kind and severity of their problems. The main therapeutic aspects of music the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Interactive music can have immediate and positive effects on the engagement of dementia subjects with apathy and has been demonstrated to improve mood states (Magee & Davidson, 2002). Furthermore, music therapy has been found to reduce symptoms of severe mental illness (Silverman & Marcionetti, 2004) as well as behavioural disorders in children and adolescents (Gold et al, 2004;Gold, Wigram & Berger, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Interactive music can have immediate and positive effects on the engagement of dementia subjects with apathy and has been demonstrated to improve mood states (Magee & Davidson, 2002). Furthermore, music therapy has been found to reduce symptoms of severe mental illness (Silverman & Marcionetti, 2004) as well as behavioural disorders in children and adolescents (Gold et al, 2004;Gold, Wigram & Berger, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Except for preventative interventions the target of music therapy is often to reduce symptoms whatever those symptoms with different client groups are. In this data, this area was clearly taken into account in only one research publication (Gold et al, 2001). Also, very specific areas like emotional synchronicity were rarely mentioned ) and the texts remained commonly on a more general level.…”
Section: Effects Of Music Therapymentioning
confidence: 81%
“…Aasgaard 2005;Ayson, 2008;Barrera & Rykov, 2002;Bruce & High, 2012;Drake, 2008;Dun, 1999;Dun, 2007;Gfeller, 1990;Hadley, 1996;Hall, 2012;Hendon & Bohon, 2008;Kim et al, 2009;Lecourt, 1991;Lindenfelser et al 2012;Loth, 2008;Oldfield, 1991;Oldfield, 1993;Shoemark & Dearn, 2008;Thompson, 2012 b. Dun, 1999;Dun, 2007;Edwards, 1994;Pasiali, 2012b;Shoemark, 1999;Shoemark, 2004 c. Dun, 2007;Lindenfelser et al, 2008;Nall & Everitt, 2005;O´Callaghan & Jordan, 2011;Rees, 2005;Shoemark, 2004 d. Dun, 1995;Elefant & Wigram 2005;Finnigan & Starr, 2010;Gfeller, 1990;Kim et al, 2009;Oldfield, 1991;Skewes & Thompson, 2009;Tomlinson, 2010 e. Ayson, 2008;Dun, 2007;Gold et al, 2001 Supportive factors (33 different texts) a. emotional support and ...…”
Section: Specific Findingsmentioning
confidence: 99%
“…A small number of randomised controlled trials have shown positive benefits of combination music and psychotherapy compared to treatment as usual in children, with higher rates of remission of anxiety disorders (Goldbeck & Ellerkamp, 2012) and a reduction in Child Behaviour Checklist scores (Gold et al 2001) From the point of view of a CAMHS, several benefits to the group emerged. It provided a youth friendly, non-clinical and safe environment that represented a space away from intense therapy sessions or medication reviews.…”
Section: Discussionmentioning
confidence: 99%